2011
DOI: 10.1177/0884533611403007
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Causing Neonatal Dyslipidemia

Abstract: Lipid abnormalities in children have become more common in recent decades. This trend is related to the increase in overweight and obesity. The 2002 National Health and Nutrition Examination Survey reported that the percentage of risk for overweight and overweight in children aged > 6 years is 31%, higher than the previous surveys. Serum lipids tend to increase quickly up to 6 months of age and reach values very close to adult values by age 2. As suggested by the American Heart Association, serum lipid values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Extremes of nutritional status and obesity have been reported to be associated with dyslipidemia among children without HIV infection [28,29,30]. In the current study, nutrition state was associated with dyslipidemia among treatment naïve HIV-infected children but was not associated with dyslipidemia among cART experienced children.…”
Section: Discussionsupporting
confidence: 40%
“…Extremes of nutritional status and obesity have been reported to be associated with dyslipidemia among children without HIV infection [28,29,30]. In the current study, nutrition state was associated with dyslipidemia among treatment naïve HIV-infected children but was not associated with dyslipidemia among cART experienced children.…”
Section: Discussionsupporting
confidence: 40%
“…Nobili and collaborators (25) showed that of 90 Italian children with biopsy-proven NAFLD, almost 40% were classified as small for gestational age compared with 7% of control subjects. Dyslipidemia has also been characterized in newborns and in children with severe undernutrition (12,34). The mechanisms by which malnutrition or growth retardation could lead to steatosis are not understood.…”
Section: Discussionmentioning
confidence: 99%